2006
DOI: 10.2486/indhealth.44.652
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in Utero and Lactational Exposure to Di(2-ethylhexyl)phthalate on Somatic and Physical Development in Rat Offspring

Abstract: Di(2-ethylhexyl)phthalate (DEHP) has been reported to act as an antiandrogen and to affect the reproductive organs and accessory genital glands. Thus, to assess the reproductive toxicity of DEHP it is important to examine both its adverse effects on the development of offspring following maternal exposure and its effects on sexual function and fertility. In the present study, we examined whether in utero and lactational exposure to DEHP affects postnatal somatic growth of offspring in the rat. Pregnant females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…32, 33 Evidence supporting this hypothesis was observed by Schmidt et al 33 in their findings that exposing mice to a diet containing low doses (0.05 and 5 mg DEHP per kg per day, corresponding to a daily intake of 0.00102 and 0.108 DEHP per kg per day) of DEHP in utero and during lactation resulted in increased visceral fat and body weight in adult offspring. In agreement with previous work in rats, 13, 35 we did not observe changes in total body weight. It remains to be determined whether a differential fat distribution is induced by DEHP without modifying the total weight of the animals and whether more drastic changes would develop later in time during senescence.…”
Section: Discussionsupporting
confidence: 94%
“…32, 33 Evidence supporting this hypothesis was observed by Schmidt et al 33 in their findings that exposing mice to a diet containing low doses (0.05 and 5 mg DEHP per kg per day, corresponding to a daily intake of 0.00102 and 0.108 DEHP per kg per day) of DEHP in utero and during lactation resulted in increased visceral fat and body weight in adult offspring. In agreement with previous work in rats, 13, 35 we did not observe changes in total body weight. It remains to be determined whether a differential fat distribution is induced by DEHP without modifying the total weight of the animals and whether more drastic changes would develop later in time during senescence.…”
Section: Discussionsupporting
confidence: 94%
“…We demonstrated in this study that DEHP and Flu interfered with the development of reproductive organs in a dose-dependent manner, in agreement with previous reports [12,26]. A decrease in the testicular, epididymal and prostate weights was caused by in utero Flu exposure.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, in utero exposure to DEHP and Flu caused an increase in the number of nipples and /or areolae in a dose-dependent manner. Our results are in agreement with the previous reports [22,25].We demonstrated in this study that DEHP and Flu interfered with the development of reproductive organs in a dose-dependent manner, in agreement with previous reports [12,26]. A decrease in the testicular, epididymal and prostate weights was caused by in utero Flu exposure.…”
supporting
confidence: 83%
“…The weight of the seminal vesicle plus coagulating glands (androgen-dependent tissues) in adult rats was also significantly reduced after exposure to 475 mg/kg DEHP, although only this dose caused significant serum testosterone levels [38]. Doses below 400 mg/kg DEHP had no effects on weights of these androgen-dependent organs and testosterone levels [38,41]. However, the gene profiles of in utero and lactational exposures to DEHP in our study were a little bit different from those reported by Culty et al [34].…”
Section: In Utero and Lactational Exposures To Dehp And Alc Dysfunctionmentioning
confidence: 92%